Doing the Gospel local congregations in ministry - Nichols, Roy C., 1918- (Nashville, TN Abingdon, 1990)
Includes bibliographical references.
Keywords: Church ministry -- United Methodist Church (US).; Pastoral theology -- Methodist Church; Lay ministry -- United Methodist Church (US).